(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The Philippines has implemented the K-12 educational system in 2013, and its impact was felt by 2016. Given the opportunity to support and achieve the government’s goal in the implementation of the K-12 system, the researchers conducted this study to determine the extent of implementation of the K-12 Basic Education Program in Bestlink College of the Philippines (BCP). The goal of this study was to determine if the Senior High School (SHS) Department of BCP created a functional basic education system that will produce productive and responsible citizens equipped with essential competencies and skills for life-long learning and employment. This study utilized descriptive quantitative research method to measure the extent of implementation of the K-12 Basic Education Program in BCP S.Y. 2018–2019 as assessed by 40 part-time public SHS teachers and 40 full-time SHS teachers of BCP in terms of seven variables, such as vision, mission, goals and objectives (VMGO), instructional program, curriculum, faculty, students’ services, facilities, and ministration and governance. The results of this study revealed that the extent of implementation of the K-12 Basic Education Program has no significant difference in terms of vision, mission, goals and objectives, instructional program, curriculum, faculty, students’ services, facilities, and administration and governance. This result was ascertained by the overall weighted mean of 4.14, which was interpreted as highly implemented as assessed by part-time public high school teachers, and an overall weighted mean of 4.33, which was interpreted as highly implemented as assessed by full-time BCP SHS teachers. All institutions should offer grade and secondary levels to determine the extent of the implementation of the K-12 Program of their respective Basic Education Program of the Department of Education. The results of the assessments and evaluations of the said program will pave the way to reach the main objectives of the program, that is, to improve Filipino students’ skills in Mathematics, Science, and Linguistics to further exhibit competence in the global job market. With the new curriculum, the Department of Education promises to offer higher-quality education through the strands. The implementation of the K-12 program in BCP implies enhancement of the learners’ basic skills, produce more competent citizens, and prepare graduates for lifelong learning and employment.